The SDGs in Africa, in the fight for human rights - Libório, Tânia (2021)
In today's world, it is essential to reflect on the problematization of the values and role of NGOs in the scope of solidarity and volunteering. They promote the personal, social and cultural development of individuals, making them part of active and committed citizenship in this world that shows so little solidarity. In this sense, it is important that we all have our eyes on solidarity movements and that we are the first players to help, defend and cooperate, in different areas with other realities. In this global era, where wealth and poverty interact, showing their potentialities and vulnerabilities, the conviction emerges to face this diversity through cooperation in the name of education and the attitudes they can transform. NGOs play a catalytic role capable of promoting development in cooperation with the achievement of the SDGs - Sustainable Development Goals. This article aims to present the missions carried out on the African continent, in favour of the achievement of the SDGs stipulated by the UN; these missions are integrated into projects carried out by volunteers from a Portuguese NGO, AMI - Assistência Médica Internacional (International Medical Assistance) and demonstrate how their work promotes cooperation and sustainable development in the communities where they operate, as well as the defence of Human Rights. We cannot ignore a global solidarity movement. Volunteers contribute in a fundamental way to cooperation and aid the countries that need it the most. We believe that the main “weapon” of a country's development is education for Human Rights.